Severe atypical HUS caused by CFH S1191L - case presentation and review of treatment options - De, Sudarsana; Waters, Aoife M.; Segal, Audrey O.; Trautmann, Agnes; Harvey, Elizabeth A.; Licht, Christoph (Pediatric nephrology, 2010)
Atypical hemolytic uremic syndrome (aHUS) has been associated with defective regulation of the alternative complement pathway. Although the use of plasma therapy is recommended, there is little consensus on the optimal treatment regimen. The outcome in many cases remains poor despite an improvement in our understanding of the pathology of aHUS. We have followed a female patient with aHUS associated with heterozygous complement Factor H (CFH) mutation (S1191L) over a period of 15 years. She has been plasma dependent since infancy and has subsequently progressed to end stage kidney disease (ESKD) requiring dialysis treatment. Despite ESKD she still depends on regular plasma infusions to prevent thrombocytopenia. The long-term treatment plan for this patient is challenging. Renal transplantation in patients with the S1191L mutation of the CFH gene carries a high risk of failure due to recurrence of aHUS in the renal graft. Thus, the only available curative treatment seems to be combined liver-kidney transplantation, covered by intensive plasma therapy, which comes with a high risk of morbidity and mortality. Antibodies against key activating components of the complement cascade may provide a promising alternative therapeutic strategy in the future. Eculizumab, a monoclonal humanized anti-C5 antibody, has recently been shown to be effective and well-tolerated in patients with paroxysmal nocturnal hemoglobinuria by preventing complement-mediated lysis of affected erythrocytes. Treatment of our patient with eculizumab is supported by recent reports on its successful use in two (pediatric and adult) patients with complement-based aHUS.